Prepreg and preparation method and application thereof

By using a combination of laminated adhesive layer and thermal filler in the circuit substrate of the semi-cured sheet, and by regulating the thickness, volatile content and curing degree of the second adhesive layer, the contradiction between the thermal conductivity of the existing circuit substrate and the peel strength and dielectric loss is solved, and the comprehensive performance of high thermal conductivity, low dielectric loss and high peel strength is achieved.

CN119872023APending Publication Date: 2025-04-25ZHEJIANG WAZAM NEW MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411997997.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

While improving thermal conductivity, the existing circuit substrates are prone to affect the interlayer bonding force and copper foil bonding force of the semi-cured sheet, resulting in poor peeling strength and increased dielectric loss, which cannot meet the usage requirements.

Method used

A semi-cured sheet is adopted, which includes a reinforcing material layer and a first glue layer and a second glue layer sequentially stacked. The first glue layer and the second glue layer permeate each other to form an interlaced layer. The first glue layer contains a first thermally conductive filler and a first resin, the second glue layer contains a second thermally conductive filler and a second resin, and the curing degree is regulated within a suitable range by defining the relationship between the thickness, volatile content and curing degree of the second glue layer.

Benefits of technology

The circuit substrate has high thermal conductivity, low dielectric loss performance and high peel strength performance, avoiding the problems of high dielectric loss and poor peel strength caused by the addition of thermally conductive fillers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119872023A_ABST
    Figure CN119872023A_ABST
Patent Text Reader

Abstract

The invention relates to a prepreg and a preparation method and application thereof. The prepreg comprises a reinforcing material layer, a first adhesive layer and a second adhesive layer, the first adhesive layer and the second adhesive layer are sequentially stacked on at least one surface of the reinforcing material layer, the first adhesive layer and the second adhesive layer are mutually permeated at the stacking position to form a staggered layer, the first adhesive layer comprises first resin and first heat conduction filler, and the second adhesive layer comprises second resin and second heat conduction filler. Wherein the thickness x, the volatile component y and the curing degree z of the second adhesive layer meet the following relational expressions: 75-0.6 x < = z < = 85-0.5 x, 80-6y < = z < = 90-6y, 50 < = x < = 120, and 5 < = y < = 10. The circuit substrate prepared from the prepreg has high heat conduction performance, low dielectric loss performance and high peel strength performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic industry, in particular to a prepreg and a preparation method and application thereof. Background Art

[0002] With the development of 5G and even 6G communications, higher requirements are placed on the thermal conductivity and dielectric loss performance of circuit substrates.

[0003] In order to improve the thermal conductivity of the circuit substrate, the existing circuit substrate usually uses a thermally conductive filler with a high thermal conductivity coefficient. However, during use, the existing thermally conductive filler with a high thermal conductivity coefficient can easily affect the interlayer bonding strength of the prepreg and the bonding strength between the prepreg and the copper foil, thereby resulting in poor peel strength of the circuit substrate. At the same time, due to the interface effect between the filler with a high thermal conductivity coefficient and the reinforcing material, the dielectric loss will also increase, which cannot meet the use requirements. Summary of the invention

[0004] Based on this, it is necessary to provide a prepreg and a preparation method and application thereof to address the above problems. The circuit substrate made of the prepreg can have high thermal conductivity, low dielectric loss and high peel strength.

[0005] A semi-cured sheet, the semi-cured sheet comprising a reinforcing material layer and a first adhesive layer and a second adhesive layer sequentially stacked on at least one surface of the reinforcing material layer, wherein the first adhesive layer and the second adhesive layer mutually penetrate each other at the stacking position to form a staggered layer, the first adhesive layer comprising a first resin and a first thermally conductive filler, the second adhesive layer comprising a second resin and a second thermally conductive filler, wherein the thickness x, volatile matter y and curing degree z of the second adhesive layer satisfy the following relationship: 75-0.6x≤z≤85-0.5x, 80-6y≤z≤90-6y, wherein 50≤x≤120, 5≤y≤10.

[0006] In one embodiment, the thickness of the first adhesive layer is 2 μm-40 μm.

[0007] In one of the embodiments, the first thermally conductive filler is a non-flaky thermally conductive filler;

[0008] And / or, the first resin is at least one of polybutadiene, a copolymer of polybutadiene and styrene, polyisoprene, modified polybutadiene, a block copolymer or graft copolymer capable of copolymerization and cross-linking reaction, a thermosetting liquid crystal resin, cyanate ester, polyphenylene ether, modified polyphenylene ether, and polyimide.

[0009] In one embodiment, the thickness of the interlaced layer is 2 μm-40 μm.

[0010] In one embodiment, the second thermally conductive filler is a sheet-shaped thermally conductive filler;

[0011] And / or, the maximum particle size D of the second thermally conductive filler 100 80%-100% of the total thickness of the second adhesive layer and the interlaced layer;

[0012] And / or, the median particle size D of the second thermally conductive filler 50 The thickness is 40%-80% of the total thickness of the second adhesive layer and the interlaced layer.

[0013] In one embodiment, the mass ratio of the second thermally conductive filler to the second resin is 2:3-4:1;

[0014] And / or, the second resin is selected from at least one of polybutadiene, copolymers of polybutadiene and styrene, polyisoprene, modified polybutadiene, block copolymers or graft copolymers capable of copolymerization and crosslinking, thermosetting liquid crystal resins, cyanate esters, polyphenylene ether, modified polyphenylene ether, and polyimide.

[0015] A method for preparing the prepreg as described above comprises the following steps:

[0016] Providing a first glue solution and a second glue solution;

[0017] Placing the first adhesive solution on at least one surface of the reinforcing material to prepare a prefabricated first adhesive layer;

[0018] The second adhesive solution is placed on the surface of the prefabricated first adhesive layer to prepare the second adhesive layer, and the first adhesive layer is formed at the same time to obtain a prepreg.

[0019] In one embodiment, the thickness x, volatile matter y and curing degree z of the prefabricated first adhesive layer satisfy the following relationship: 70-0.6x≤z≤86-0.6x, 75-7y≤z≤85-5.5y, wherein 10≤x≤50, 1≤y≤5.

[0020] A circuit substrate made of the prepreg described above.

[0021] A printed circuit board made of the circuit substrate as described above.

[0022] In the prepreg of the present invention, by arranging the first thermally conductive filler in the first adhesive layer and the second thermally conductive filler in the second adhesive layer, the circuit substrate prepared by the prepreg has good thermal conductivity. At the same time, by defining the relationship between the thickness x of the second adhesive layer, the volatile matter y and the curing degree z, the curing degree of the second adhesive layer can be adjusted to be within a suitable range, that is, the optimal curing degree range, according to the value of the thickness x or the volatile matter y of the second adhesive layer. In addition, the relationship between the thermal conductivity, dielectric loss and peel strength of the circuit substrate prepared by the prepreg can be effectively balanced in coordination with the thickness and volatile matter of the second adhesive layer, so that the prepared circuit substrate has high thermal conductivity, low dielectric loss and high peel strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 It is a schematic structural diagram of a prepreg according to a first embodiment of the present invention;

[0025] Figure 2 Schematic diagram of the structure of a prepreg according to a second embodiment of the present invention.

[0026] Reference numerals:

[0027] 1. Reinforcement material layer; 2. First adhesive layer; 3. Interlaced layer; 4. Second adhesive layer. DETAILED DESCRIPTION

[0028] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0030] Combination Figure 1-2 As shown, the prepreg provided by the present invention comprises a reinforcing material layer 1 and a first adhesive layer 2 and a second adhesive layer 4 sequentially stacked on at least one surface of the reinforcing material layer 1, and the first adhesive layer 2 and the second adhesive layer 4 are mutually infiltrated at the stacking position to form a staggered layer 3. It can be understood that the provision of the staggered layer 3 effectively ensures that the first adhesive layer 2 and the second adhesive layer 4 in the prepreg are not delaminated, thereby improving the quality stability of the prepreg.

[0031] After in-depth research, the applicant found that the thermal conductivity and dielectric loss performance of the circuit substrate are mainly affected by the thickness of the second adhesive layer 4. At the same time, the peel strength of the circuit substrate, that is, the bonding strength between the semi-cured sheet and the conductive layer, such as copper foil, is mainly affected by the volatile matter of the second adhesive layer 4, and the dielectric loss and peel strength of the circuit substrate are mainly affected by the curing degree of the second adhesive layer 4. There are specific relationships between the thickness x, volatile matter y and curing degree z of the second adhesive layer 4, such as 75-0.6x≤z≤85-0.5x, 8 0-6y≤z≤90-6y. According to the corresponding relationship, the curing degree of the second adhesive layer 4 can be adjusted to be within a suitable range, that is, the optimal curing degree range, according to the thickness or volatile matter of the second adhesive layer 4. In coordination with the thickness and volatile matter of the second adhesive layer 4, the relationship between the thermal conductivity, dielectric loss and peel strength of the circuit substrate prepared using the semi-cured sheet can be balanced, so that the prepared circuit substrate has high thermal conductivity while still having low dielectric loss and high peel strength under the premise of the presence of thermally conductive filler.

[0032] To this end, in the present invention, the first adhesive layer 2 includes a first resin and a first thermally conductive filler, the second adhesive layer 4 includes a second resin and a second thermally conductive filler, and the thickness x, volatile matter y and curing degree z of the second adhesive layer 4 satisfy the following relationship: 75-0.6x≤z≤85-0.5x, 80-6y≤z≤90-6y, wherein 50≤x≤120, 5≤y≤10. It can be understood that in the present invention, the thickness x of the second adhesive layer 4 is 50μm-120μm, the volatile matter y is 5%-10%, and the unit of curing degree z is %, and the above calculation formula only involves the conversion between numerical values, and does not involve the conversion of units. Moreover, in the present invention, the thickness of the second adhesive layer 4 is the thickness of the second adhesive layer 4 on a single side.

[0033] It can be understood that in the present invention, by setting the first thermally conductive filler in the first adhesive layer 2 and setting the second thermally conductive filler in the second adhesive layer 4, the circuit substrate prepared by the prepreg has good thermal conductivity, and by limiting the relationship between the thickness x of the second adhesive layer 4, the volatile matter y and the degree of cure z, the degree of cure of the second adhesive layer 4 is regulated to be within a suitable range, and the thickness and volatile matter of the second adhesive layer 4 are coordinated, and the relationship between the thermal conductivity, dielectric loss and peel strength of the circuit substrate made of the prepreg can be effectively balanced, and the problem of high dielectric loss and poor peel strength of the circuit substrate caused by the addition of thermally conductive fillers can be effectively avoided. Moreover, the setting of the first adhesive layer in the present invention can effectively improve the interface effect between the second thermally conductive filler and the reinforcing material, and further reduce the dielectric loss of the circuit substrate. Therefore, the circuit substrate prepared by the prepreg of the present invention has both high thermal conductivity, low dielectric loss performance and high peel strength performance.

[0034] Optionally, the second thermally conductive filler is in the form of a sheet, preferably at least one of sheet-shaped boron nitride, sheet-shaped silicon nitride or sheet-shaped silicon carbide. This configuration can improve the thermal conductivity of the circuit substrate while helping to reduce the dielectric loss of the circuit substrate.

[0035] Optionally, the maximum particle size D of the second thermally conductive filler is 100 is 80%-100% of the total thickness of the second adhesive layer 4 and the interlaced layer 3; further, the median particle size D 50 It is 40%-80% of the total thickness of the second adhesive layer 4 and the interlaced layer 3. It can be understood that the total thickness of the second adhesive layer 4 and the interlaced layer 3 is the sum of the thickness of the single-sided second adhesive layer 4 and the thickness of the single-sided interlaced layer 3. In this way, under the premise of limiting the thickness of the second adhesive layer 4, the maximum particle size D of the thermal conductive filler is adjusted. 100 And the median particle size D 50, which is beneficial to improving the thermal conductivity of the thermal conductive filler and reducing the thermal anisotropy of the circuit substrate, further improving the overall thermal conductivity of the circuit substrate; at the same time, it is beneficial to improve the stability of the second adhesive layer 4 and the prepreg, thereby reducing the dielectric loss of the circuit substrate and improving the peeling strength of the circuit substrate.

[0036] It can be understood that when the second thermally conductive filler is a flake-shaped thermally conductive filler, at this time, the maximum particle size D of the second thermally conductive filler is 100 refers to the maximum length of the sheet-shaped thermally conductive filler; when the second thermally conductive filler is a spherical thermally conductive filler, at this time, the maximum particle size D of the second thermally conductive filler 100 Refers to the maximum particle size of spherical thermal conductive filler.

[0037] Optionally, the mass ratio of the second thermally conductive filler to the second resin is 2:3-4:1. With this arrangement, the thermal conductivity and dielectric loss of the circuit substrate can be better controlled by adjusting the mass ratio of the second thermally conductive filler to the second resin.

[0038] In the present invention, the second resin is selected from a low dielectric resin, the dielectric constant of the low dielectric resin is 2-4, and the low dielectric resin is preferably at least one of polybutadiene, a copolymer of polybutadiene and styrene, polyisoprene, modified polybutadiene, a block copolymer or graft copolymer capable of copolymerization and crosslinking reaction, a thermosetting liquid crystal resin, cyanate ester, polyphenylene ether, modified polyphenylene ether, and polyimide. Such a configuration is conducive to reducing the dielectric loss of the circuit substrate.

[0039] Optionally, the thickness of the first adhesive layer 2 is 2 μm-40 μm. Specifically, the thickness of the first adhesive layer 2 includes but is not limited to 2 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, and 40 μm. In this way, while ensuring that the circuit substrate has high thermal conductivity, the bonding force between the layers in the prepreg can be effectively improved, thereby effectively improving the peel strength of the circuit substrate.

[0040] It should be noted that the thickness of the first adhesive layer 2 in the present invention refers to the thickness of the first adhesive layer 2 on one side.

[0041] In the present invention, the first thermally conductive filler is a non-flaky thermally conductive filler. It can be understood that in the present invention, the non-flaky thermally conductive filler is a filler without a flat surface morphology, such as spherical, irregular particle shape, such as angular, prismatic, hexagonal, etc. It is further preferred to be spherical aluminum oxide, angular aluminum oxide, spherical silicon dioxide, angular silicon dioxide, prismatic silicon nitride, hexagonal silicon nitride, spherical silicon nitride, prismatic silicon carbide, hexagonal silicon carbide, spherical silicon carbide, etc. Such a setting is conducive to improving the dispersibility of the first thermally conductive filler in the first adhesive layer 2, improving the bonding force between the first adhesive layer 2 and the reinforcing material layer 1, and then improving the thermal conductivity and peeling strength of the circuit substrate.

[0042] Furthermore, the median particle size of the non-flaky thermally conductive filler is 2 μm-10 μm. This configuration is beneficial for further improving the thermal conductivity and peeling strength of the circuit substrate.

[0043] In the present invention, the first resin is selected from a low dielectric resin, the dielectric constant of the low dielectric resin is 2-4, and the low dielectric resin is preferably at least one of polybutadiene, a copolymer of polybutadiene and styrene, polyisoprene, modified polybutadiene, a block copolymer or graft copolymer capable of copolymerization and cross-linking reaction, a thermosetting liquid crystal resin, a cyanate ester, a polyphenylene ether, a modified polyphenylene ether, and a polyimide.

[0044] In one embodiment, the mass ratio of the non-flaky thermally conductive filler to the first resin is 1:9-3:7. In this way, by adjusting the mass ratio of the non-flaky thermally conductive filler to the first resin in the first adhesive layer 2, higher peel strength and thermal conductivity can be obtained.

[0045] It can be understood that, in the present invention, the specific types of the first resin in the first adhesive layer 2 and the second resin in the second adhesive layer 4 may be the same or different, but are preferably the same.

[0046] It can be understood that, since the first adhesive layer 2 includes the first resin and the first thermally conductive filler, and the second adhesive layer 4 includes the second resin and the second thermally conductive filler, the interlaced layer 3 formed by the mutual penetration of the first adhesive layer 2 and the second adhesive layer 4 at the stacking position must contain the first thermally conductive filler and the second thermally conductive filler that are interlaced with each other, and a cross-linking reaction will also occur between the first resin and the second resin. At this time, in the present invention, the thickness of the interlaced layer 3 is the distance between the second thermally conductive filler closest to the first adhesive layer 2 and the first thermally conductive filler closest to the second adhesive layer 4.

[0047] Optionally, the thickness of the staggered layer 3 is 2 μm-40 μm; specifically, the thickness of the staggered layer 3 includes but is not limited to 2 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, and 40 μm. Such a configuration can improve the bonding force between the layers in the prepreg, further improve the peeling strength of the circuit substrate, and at the same time be beneficial to further improve the thermal conductivity of the circuit substrate and effectively reduce the dielectric loss of the circuit substrate.

[0048] In one embodiment, the reinforcing material layer 1 is selected from glass fiber cloth and the like.

[0049] At the same time, the present invention also provides a method for preparing a prepreg, comprising the following steps:

[0050] S1, providing a first glue solution and a second glue solution;

[0051] S2, placing the first adhesive solution on at least one surface of the reinforcing material to prepare a prefabricated first adhesive layer;

[0052] S3, placing the second adhesive solution on the surface of the prefabricated first adhesive layer to prepare the second adhesive layer 4, and at the same time forming the first adhesive layer 2 to obtain a prepreg.

[0053] In step S1, the first adhesive solution includes a first resin and a first thermally conductive filler, an additive and a solvent, wherein the additive may be a curing agent and a coupling agent, etc., and the first thermally conductive filler is a non-flaky thermally conductive filler.

[0054] In one embodiment, in the first glue, based on 100 parts by weight of the first resin, the added amount of the first thermally conductive filler is 11 parts by weight to 43 parts by weight, the added amount of the curing agent is 2 parts by weight to 10 parts by weight, and the added amount of the coupling agent is 1 part by weight to 4 parts by weight.

[0055] Similarly, the second adhesive solution includes a second resin, a second thermally conductive filler, an additive and a solvent. The additive may be a curing agent and a coupling agent, etc. The second thermally conductive filler is a flaky thermally conductive filler.

[0056] In one embodiment, in the second glue, based on 100 parts by weight of the second resin, the added amount of the second thermally conductive filler is 67 parts by weight to 400 parts by weight, the added amount of the curing agent is 2 parts by weight to 10 parts by weight, and the added amount of the coupling agent is 7 parts by weight to 40 parts by weight.

[0057] It should be noted that in step S1, the specific types of the first resin in the first glue solution and the second resin in the second glue solution can be the same or different. Similarly, the specific types of the curing agent or coupling agent in the first glue solution and the curing agent or coupling agent in the second glue solution can be the same or different.

[0058] In one embodiment, the curing agent includes at least one of 2,5-dimethyl-2,5-di(benzoyl peroxide)hexane, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane, 2,5-dimethyl-2,5-di-tert-butyl peroxy-3-hexyne, and diethylpropene peroxide; the coupling agent includes at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

[0059] In step S2, the first adhesive solution is placed on at least one surface of the reinforcing material and baked to form a semi-cured prefabricated first adhesive layer, wherein the baking temperature is 100° C.-150° C. and the baking time is 30s-120s.

[0060] Optionally, the thickness x, volatile content y and curing degree z of the prefabricated first adhesive layer satisfy the following relationship: 70-0.6x≤z≤86-0.6x, 75-7y≤z≤85-5.5y, wherein 10≤x≤50, 1≤y≤5. It can be understood that the thickness x of the prefabricated first adhesive layer is 10μm-50μm, the volatile content y is 1%-5%, and the unit of curing degree z is %, and the above calculation formula only involves the conversion between numerical values, and does not involve the conversion of units.

[0061] In the present invention, by defining the relationship between the thickness x of the prefabricated first adhesive layer, the volatile content y and the curing degree z, the curing degree of the prefabricated first adhesive layer can be regulated within a suitable range according to the value of the thickness x of the prefabricated first adhesive layer or the volatile content y, which can effectively improve the bonding force between the prefabricated first adhesive layer and the reinforcing material layer 1, and effectively improve the degree of cross-linking reaction between the prefabricated first adhesive layer and the second adhesive layer 4 during the curing process, thereby regulating the thickness of the staggered layer 3, which is beneficial to improving the bonding force between the first adhesive layer 2 and the second adhesive layer 4, and further improving the stability of the semi-cured sheet, so that the peeling strength of the circuit substrate can be further improved and the dielectric loss of the circuit substrate can be reduced without affecting the thermal conductivity of the circuit substrate.

[0062] In the present invention, the specific method of placing the first adhesive on at least one surface of the reinforcing material is not limited, and can be implemented by dipping, coating, etc. Specifically, in one embodiment, the first adhesive is coated on at least one surface of the reinforcing material to form a reinforcing material having a prefabricated first adhesive layer on both sides or one side.

[0063] In another embodiment, the reinforcing material is immersed in the first adhesive solution to form a reinforcing material having prefabricated first adhesive layers on both sides.

[0064] In step S3, the second adhesive liquid is placed on the surface of the prefabricated first adhesive layer and is baked to form a semi-cured second adhesive layer 4. During this process, the second adhesive liquid and the prefabricated first adhesive layer penetrate and react with each other to form an interlaced layer 3 and a first adhesive layer 2, wherein the baking reaction temperature is 100-150°C and the baking time is 60-300s.

[0065] In one embodiment, the second adhesive solution is coated on the surface of the prefabricated first adhesive layer, or the reinforcing material with the prefabricated first adhesive layer is immersed in the second adhesive solution.

[0066] In addition, the present invention also provides a circuit substrate made of the prepreg as described above. The circuit substrate has high thermal conductivity, low dielectric loss and high peel strength. Specifically, in one embodiment, the thermal conductivity of the circuit substrate is ≥0.65 W / m·k, the dielectric loss is ≤0.0027, and the peel strength is ≥0.52 N / mm.

[0067] And, a printed circuit board made of the circuit substrate as described above.

[0068] Specifically, the printed circuit board is mainly made of the circuit substrate through processes such as drilling, hole filling, micro-etching, pre-preg, activation, acceleration, chemical copper and copper thickening.

[0069] Hereinafter, the semi-cured sheet and its preparation method and application will be further described by the following specific examples. However, it will be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0070] It should be noted that the thickness of the prefabricated first adhesive layer, the thickness of the first adhesive layer, the thickness of the second adhesive layer, and the thickness of the interlaced layer involved in the embodiments of the present invention and the comparative examples are all thicknesses corresponding to a single side, and are all measured by conventional means; at the same time, the volatile matter of the prefabricated first adhesive layer and the volatile matter of the second adhesive layer are also measured by conventional means.

[0071] Example 1

[0072] 100 parts by weight of polybutadiene (dielectric constant 2.2), 25 parts by weight of spherical alumina (D 50 6 μm), 80 parts by weight of xylene, 10 parts by weight of dicumyl peroxide and 5 parts by weight of KH560 coupling agent were mixed to obtain a first glue solution; 100 parts by weight of polybutadiene (dielectric constant is 2.2), 80 parts by weight of flake boron nitride (D 100 77μm, D50 45 μm), 80 parts by weight of xylene, 10 parts by weight of dicumyl peroxide and 5 parts by weight of KH560 coupling agent were uniformly mixed to obtain a second glue solution.

[0073] The glass fiber cloth was immersed in the first adhesive solution obtained above, and then a double-sided prefabricated first adhesive layer was formed at 130° C. for 90 seconds, wherein the thickness of the prefabricated first adhesive layer was 26 μm, the volatile matter was 3%, and the degree of curing was 60%; then the second adhesive solution obtained above was applied to the surface of the prefabricated first adhesive layer, and then baked at 88.5° C. for 400 seconds to form an interlaced layer, a first adhesive layer, and a second adhesive layer, to obtain a semi-cured sheet, wherein the thickness of the first adhesive layer was 5 μm, the thickness of the interlaced layer was 21 μm, the thickness of the second adhesive layer was 65 μm, the volatile matter was 7.5%, and the degree of curing was 40%.

[0074] Four prepregs obtained above were stacked, and then covered with copper foil on both sides and pressed to obtain a circuit substrate.

[0075] Example 2

[0076] 100 parts by weight of polyphenylene ether (dielectric constant 2.4), 11 parts by weight of spherical silica (D 50 6 μm), 80 parts by weight of xylene, 10 parts by weight of dicumyl peroxide and 5 parts by weight of KH560 coupling agent were mixed evenly to obtain a first glue solution; 100 parts by weight of polybutadiene (dielectric constant is 2.2), 67 parts by weight of flaky silicon nitride (D 100 46μm, D 50 23 μm), 80 parts by weight of xylene, 10 parts by weight of dicumyl peroxide and 5 parts by weight of KH560 coupling agent were mixed evenly to obtain a second glue solution.

[0077] The glass fiber cloth was immersed in the first adhesive solution obtained above, and then a double-sided prefabricated first adhesive layer was formed at 130° C. for 90 seconds, wherein the thickness of the prefabricated first adhesive layer was 10 μm, the volatile matter was 1%, and the curing degree was 73%; then the second adhesive solution obtained above was applied to the surface of the prefabricated first adhesive layer, and then baked at 88.5° C. for 400 seconds to form an interlaced layer, a first adhesive layer, and a second adhesive layer, to obtain a semi-cured sheet, wherein the thickness of the first adhesive layer was 2 μm, the thickness of the interlaced layer was 8 μm, the thickness of the second adhesive layer was 50 μm, the volatile matter was 5%, and the curing degree was 54%.

[0078] Four prepregs obtained above were stacked, and then covered with copper foil on both sides and pressed to obtain a circuit substrate.

[0079] Example 3

[0080] 100 parts by weight of polyphenylene ether (dielectric constant 2.4), 43 parts by weight of angular silica (D 50 6 μm), 80 parts by weight of xylene, 10 parts by weight of dicumyl peroxide and 5 parts by weight of KH560 coupling agent were mixed to obtain a first glue solution; 100 parts by weight of polybutadiene (dielectric constant is 2.2), 400 parts by weight of flake boron nitride (D 100 160μm, D 50 128 μm), 80 parts by weight of xylene, 10 parts by weight of dicumyl peroxide and 5 parts by weight of KH560 coupling agent were mixed evenly to obtain a second glue solution.

[0081] The glass fiber cloth was immersed in the first adhesive solution obtained above, and then a double-sided prefabricated first adhesive layer was formed at 130° C. for 90 seconds, wherein the thickness of the prefabricated first adhesive layer was 50 μm, the volatile matter was 4%, and the degree of curing was 49%; then the second adhesive solution obtained above was applied to the surface of the prefabricated first adhesive layer, and then baked at 88.5° C. for 400 seconds to form an interlaced layer, a first adhesive layer, and a second adhesive layer, to obtain a semi-cured sheet, wherein the thickness of the first adhesive layer was 10 μm, the thickness of the interlaced layer was 40 μm, the thickness of the second adhesive layer was 120 μm, the volatile matter was 10%, and the degree of curing was 22%.

[0082] Four prepregs obtained above were stacked, and then covered with copper foil on both sides and pressed to obtain a circuit substrate.

[0083] Example 4

[0084] The difference between Example 4 and Example 1 is that the flake boron nitride (D 100 77μm, D 50 45μm) is replaced by flake boron nitride (D 100 81μm, D 50 The glass fiber cloth is immersed in the first adhesive solution obtained above, and then a double-sided prefabricated first adhesive layer is formed at 130°C for 20s, wherein the thickness of the prefabricated first adhesive layer is 26μm, the volatile matter is 3%, and the curing degree is 20%; the thickness of the first adhesive layer in the semi-cured sheet is 0.5μm, the thickness of the staggered layer is 25.5μm, the thickness of the second adhesive layer is 65μm, the volatile matter is 7.5%, and the curing degree is 40%.

[0085] Example 5

[0086] Compared with Example 1, Example 5 is different only in that the glass fiber cloth is immersed in the first adhesive solution obtained above, and then a double-sided prefabricated first adhesive layer is formed at 130°C for 90s, wherein the thickness of the prefabricated first adhesive layer is 70μm, the volatile matter is 5%, and the degree of curing is 44%; the thickness of the first adhesive layer in the semi-cured sheet is 49μm, the thickness of the staggered layer is 21μm, the thickness of the second adhesive layer is 65μm, the volatile matter is 7.5%, and the degree of curing is 40%.

[0087] Example 6

[0088] The difference between Example 6 and Example 1 is that the flake boron nitride (D 100 77μm, D 50 45μm) is replaced by flake boron nitride (D 100 99μm, D 50 The glass fiber cloth is immersed in the first adhesive solution obtained above, and then a double-sided prefabricated first adhesive layer is formed at 130°C for 45s, wherein the thickness of the prefabricated first adhesive layer is 50μm, the volatile matter is 5%, and the curing degree is 40%; the thickness of the first adhesive layer in the semi-cured sheet is 5μm, the thickness of the staggered layer is 45μm, the thickness of the second adhesive layer is 65μm, the volatile matter is 7.5%, and the curing degree is 40%.

[0089] Example 7

[0090] The difference between Example 7 and Example 1 is that the flake boron nitride (D 100 77μm, D 50 45μm) is replaced by flake boron nitride (D 100 59μm, D 50 The glass fiber cloth is immersed in the first adhesive solution obtained above, and then a double-sided prefabricated first adhesive layer is formed at 130°C for 100s, wherein the thickness of the prefabricated first adhesive layer is 26μm, the volatile matter is 1%, and the curing degree is 70%; the thickness of the first adhesive layer in the semi-cured sheet is 25μm, the thickness of the staggered layer is 1μm, the thickness of the second adhesive layer is 65μm, the volatile matter is 7.5%, and the curing degree is 40%.

[0091] Example 8

[0092] The only difference between Example 8 and Example 1 is that the D of the flake boron nitride in the second glue is 100 60μm, D 50 It is 17μm.

[0093] Example 9

[0094] The difference between Example 9 and Example 1 is that spherical alumina (D 10077μm, D 50 45μm) to replace flake boron nitride (D 100 77μm, D 50 is 45μm).

[0095] Example 10

[0096] The difference between Example 10 and Example 1 is that the first glue solution uses flake boron nitride (D 50 6μm) to replace spherical alumina (D 50 is 6μm).

[0097] Comparative Example 1

[0098] Compared with Example 1, Comparative Example 1 differs only in that the second adhesive solution obtained above is coated on the surface of the prefabricated first adhesive layer, and then baked at 80°C for 400s to form an interlaced layer, a first adhesive layer and a second adhesive layer, to obtain a semi-cured sheet, wherein the thickness of the first adhesive layer is 16 μm, the thickness of the interlaced layer is 10 μm, the thickness of the second adhesive layer is 65 μm, the volatile matter is 7.5%, and the degree of curing is 35.5%.

[0099] Comparative Example 2

[0100] Compared with Example 1, Comparative Example 2 differs only in that the second adhesive solution obtained above is coated on the surface of the prefabricated first adhesive layer, and then baked at 88.5°C for 500s to form an interlaced layer, a first adhesive layer and a second adhesive layer, to obtain a semi-cured sheet, wherein the thickness of the first adhesive layer is 0.5μm, the thickness of the interlaced layer is 25.5μm, the thickness of the second adhesive layer is 65μm, the volatile matter is 7.5%, and the degree of curing is 49%.

[0101] Comparative Example 3

[0102] Compared with Example 1, Comparative Example 3 is different only in that the glass fiber cloth is immersed in the first adhesive solution obtained above, and then a double-sided prefabricated first adhesive layer is formed at 130°C for 270s, wherein the thickness of the prefabricated first adhesive layer is 26μm, the volatile matter is 3%, and the degree of curing is 100%; the thickness of the first adhesive layer in the semi-cured sheet is 26μm, the thickness of the interlaced layer is 0μm, the thickness of the second adhesive layer is 65μm, the volatile matter is 7.5%, and the degree of curing is 40%.

[0103] Comparative Example 4

[0104] Comparative Example 4 is different from Example 1 only in that the second glue solution does not contain flake boron nitride (D 100 77μm, D 50 is 45μm).

[0105] The performance tests were conducted on the circuit substrates prepared in Examples 1-10 and Comparative Examples 1-4. The test results are shown in Table 1.

[0106] Among them, peel strength performance: test method is based on GB / T 4722-2017.

[0107] Thermal conductivity: The test method is based on ASTM D5470-2017.

[0108] Dielectric loss: Test method is based on GB / T 12636-90.

[0109] Table 1

[0110]

[0111] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0112] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A prepreg, characterized in that: The semi-cured sheet includes a reinforcing material layer and a first adhesive layer and a second adhesive layer sequentially stacked on at least one surface of the reinforcing material layer, and the first adhesive layer and the second adhesive layer penetrate each other at the stacking position to form an interlaced layer, the first adhesive layer includes a first resin and a first thermally conductive filler, and the second adhesive layer includes a second resin and a second thermally conductive filler, wherein the thickness x, volatile matter y and curing degree z of the second adhesive layer satisfy the following relationship: 75-0.6x≤z≤85-0.5x, 80-6y≤z≤90-6y, wherein 50≤x≤120, 5≤y≤10.

2. The prepreg according to claim 1, characterized in that: The thickness of the first adhesive layer is 2 μm-40 μm.

3. The prepreg according to claim 1, characterized in that: The first thermally conductive filler is a non-flaky thermally conductive filler; And / or, the first resin is at least one of polybutadiene, a copolymer of polybutadiene and styrene, polyisoprene, modified polybutadiene, a block copolymer or graft copolymer capable of copolymerization and cross-linking reaction, a thermosetting liquid crystal resin, cyanate ester, polyphenylene ether, modified polyphenylene ether, and polyimide.

4. The prepreg according to claim 1, characterized in that: The thickness of the interlaced layer is 2 μm-40 μm.

5. The prepreg according to claim 1, characterized in that: The second thermally conductive filler is a flake thermally conductive filler; And / or, the maximum particle size D of the second thermally conductive filler 100 80%-100% of the total thickness of the second adhesive layer and the interlaced layer; And / or, the median particle size D of the second thermally conductive filler 50 The thickness is 40%-80% of the total thickness of the second adhesive layer and the interlaced layer.

6. The prepreg according to claim 1, characterized in that: The mass ratio of the second thermally conductive filler to the second resin is 2:3-4:1; And / or, the second resin is selected from at least one of polybutadiene, copolymers of polybutadiene and styrene, polyisoprene, modified polybutadiene, block copolymers or graft copolymers capable of copolymerization and crosslinking, thermosetting liquid crystal resins, cyanate esters, polyphenylene ether, modified polyphenylene ether, and polyimide.

7. A method for preparing a prepreg according to any one of claims 1 to 6, characterized in that: The steps include: Providing a first glue solution and a second glue solution; Placing the first adhesive solution on at least one surface of the reinforcing material to prepare a prefabricated first adhesive layer; The second adhesive solution is placed on the surface of the prefabricated first adhesive layer to prepare the second adhesive layer, and the first adhesive layer is formed at the same time to obtain a prepreg.

8. The method for preparing a prepreg according to claim 7, characterized in that: The thickness x, volatile matter y and curing degree z of the prefabricated first adhesive layer satisfy the following relationship: 70-0.6x≤z≤86-0.6x, 75-7y≤z≤85- 5.5y, where 10≤x≤50, 1≤y≤5.

9. A circuit substrate made of the prepreg according to any one of claims 1 to 6.

10. A printed circuit board made using the circuit substrate as claimed in claim 9.